Assessing six decades of rabies in the Philippines - Ralf Benjo Goder Morilla; Kathleen Laum Cabanlit; Angel Mae Frias Luga; Chin-Chin Jimenea Demayo; Jamerah Baniaga Sidic; Cesar Guinanao Demayo (International Journal of Public Health Science (IJPHS), 2023)
Despite initiatives to address the disease, rabies remains a public health threat in the Philippines. To determine the trend of rabies infections in the country and provide possible interventions to reduce or eliminate deaths of the affected, we evaluated rabies morbidity and mortality statistics over sixty years. Over the last six decades, rabies mortality rates in the Philippines have steadily decreased. The Philippines' rabies sex-specific mortality rate trend from 1960 to 2019 showed that males account for higher rabies mortality than females. People aged 70 and up have the highest mortality rate, while children under the age of 1 have the lowest. The region with the highest mortality rate in the Philippines is region II (Cagayan Valley), with 39.5. The region with the highest morbidity rate is XI (Davao region), with 148.7. The correlation value was 0.197, indicating a weak correlation between regional morbidity and mortality rates in the Philippines over the years. Hence, those who have contracted rabies are less likely to die over time. Comprehensive control measures by both the national and local government units should be strengthened to eliminate rabies in the Philippines within the next few years.